VIDEO-ASSISTED EXTENSIVE LISTENING PROGRAM TO IMPROVE PRE-SERVICE EFL TEACHERS’ LISTENING SKILLS - Rina Astuti Purnamaningwulan (University of Muhammadiyah Malang, 2021)
Listening is an essential skill from which learners can acquire a vast amount of language input. Pre-service English teachers need to have excellent listening skills as they are demanded to develop meaning through various listening activities to prepare themselves to be qualified EFL teachers. A video-assisted Extensive Listening (EL) program was administered to facilitate pre-service EFL teachers to improve their listening skills. Using a quasi-experimental design, this research aimed to see whether there was a significant difference between the listening skill of pre-service teachers who received a video-assisted EL program for one semester and those who received regular instructions. Fifty-two pre-service teachers taking the Intermediate Listening course participated in this study. The participants were randomly assigned to two classes, namely the control group and the experimental group respectively. The quantitative data were collected from both groups' post-test results. An independent sample t-test that was performed to compare the post-test scores of both groups showed a non-significant result (t = 0.757, p >.05). Therefore, it can be concluded that the difference in scores between the experimental and the control group was not significant. This adventitious empirical result might have resulted from the swift change to emergency online learning due to the Covid-19 pandemic.